No peace [large type] - Best, James D., 1945- (Best, James D., 1945- Steve Dancy tale, 2020)
"After marriage, Steve Dancy has quietly settled in San Diego. He can hardly remember his days of wanderlust, and he's grateful to have left behind the violence of a raw frontier. In a celebratory mood, Steve invites his mother to a meet her new grandchild in a chic resort in Monterey, California. With the delivery of a handwritten note, his world suddenly reverts to the savagery of his bygone days. There will be no peace"--Provided by publisher.